2016
DOI: 10.1071/mf15419
|View full text |Cite
|
Sign up to set email alerts
|

Socio-ecological aspects of sustaining Ramsar wetlands in three biodiverse developing countries

Abstract: Integrating conservation and ecologically sustainable development of wetlands is a major challenge, especially in developing countries. While many developing countries harbour significant biodiversity and socio-cultural resources, they have substantial development pressures. We explore the similarities in issues around wetland conservation and sustainability in three developing countries using case studies of internationally significant wetlands in Tanzania, Colombia and Papua New Guinea. We examine key aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This migration of the rural population to the urban areas of the country does not generate the revenues that the peasants expect, on the contrary, many of the villagers who leave the countryside contribute to increasing misery and violence in the cities [64]. In addition to the low profitability, as a cause of migration of the inhabitants, the absence of the state (seen in the lack of basic services and infrastructure) [14,42,65] and the armed conflict [61], have promoted this phenomenon, bringing with it the displacement of people with a historical legacy in these territories. The absence of these people in the Páramos implies a series of negative consequences, for example, the entry of new people into these areas, without any traditional practical knowledge about the territory and its millenary management.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This migration of the rural population to the urban areas of the country does not generate the revenues that the peasants expect, on the contrary, many of the villagers who leave the countryside contribute to increasing misery and violence in the cities [64]. In addition to the low profitability, as a cause of migration of the inhabitants, the absence of the state (seen in the lack of basic services and infrastructure) [14,42,65] and the armed conflict [61], have promoted this phenomenon, bringing with it the displacement of people with a historical legacy in these territories. The absence of these people in the Páramos implies a series of negative consequences, for example, the entry of new people into these areas, without any traditional practical knowledge about the territory and its millenary management.…”
Section: Resultsmentioning
confidence: 99%
“…Available information usually refers to specific areas and locations and statistics are made at a local level to estimate population, cultivated land and crops, livestock species, and production systems [2]. From an environmental and ecological point of view the Páramo landscapes of the study area provide ecosystem services mainly related to biodiversity [15,24], collection and water supply [9,12] and among the anthropic activities typical of these Colombian ecosystems, the dual purpose cattle ranching [6,20], while ecotourism is also affirmed [14,25] (Figure 3). Economic activities of local products are mainly oriented towards local markets, to emergent markets in periods of increasing population and to city markets.…”
Section: Area Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…There is scope for broadening its use to more holistic forms of management, including from narratives based on palaeoecological analyses about past changes and projected management. Lynch et al (2016) Case studies identified inadequate inventory, survey and monitoring as well as significant risks to wetlands. Guidance for the wise use of wetlands could assist in addressing the loss and degradation.…”
Section: Authorsmentioning
confidence: 99%